Creating PRODUCTIVE Workers in Industrial Context from the Definition of Thermal Comfort - Morgado, Mariana; Teixeira, Leonor; Talaia, Mário (International Journal of Industrial Engineering and Management, 2015)
The human action among environment concerns and countries development is being debated by several authors. Thermal comfort is an extremely broad concept directly related to ergonomics, energy buildings consumption and workers’ performance. The present paper intends to analyse the thermal environment inside of a Portuguese manufacturing metalworking industry in order to understand its influence in worker’s performance and well-being. For this purpose, two types of studies were conducted: analytical and empirical. The analytical exploration regards the indoor thermal environment study concerning two thermal indexes: EsConTer and THI. The empirical exploration consists in workers’ thermal sensation study, regarding a thermal colour scale based in ASHRAE seven-point thermal scale. Therefore a measuring instrument was used, ‘Testo 435-4’, to collect air temperature (ºC), air relative humidity (%) and wet bulb temperature (ºC) data. The EsConTer index was the most surprising applied method since it showed itself capable to describe the thermal environment of an industrial space due to its correlation with THI, and at the same time adequate to define workers’ thermal sensation. Moreover, the authors consider thermal environment studies in workplaces an important aspect to improve the productivity of workers in business contexts. Article history: Received (28.09. 2014); Revised (27.05.2015); Accepted (29.06.2015)